Band-pass tunable filter based on planar dielectric resonators - Buslov,OY; Keys,VN; Kozyrev,AB; Shimko,AY; Alford,NMN; Petrov,PK (2008)
An X-band 2-pole filter based on uniplanar dielectric resonators (PDR) with ferroelectric tuning was designed and fabricated. PDR's were chosen because of their high Q-factor and the rarefied spectrum of resonance mode frequencies. At frequency ~10.5GHz the filter displayed insertion losses not more than S 21=-3dB in the bandwidth Δf=110MHz. The frequency of tuning was ΔF=420MHz. © 2008: CriMiCo'2008 Organizing Committee.